Occupational risk factors related to musculoskeletal disorders among Praewa silk weavers in the Northeast region, Thailand - Yota, Wuttichai; Neubert, Manida S.; Kaewdok, Teeraphun (Narra J, 2025)
Praewa silk weavers are subject to numerous occupational risk factors that contribute to musculoskeletal disorders (MSDs), primarily due to inadequate occupational safety measures, limited access to health services, and substandard working conditions. The aim of this study was to assess the prevalence rate and determinants of MSDs among Praewa silk weavers. A cross-sectional study employing a convenience sampling method was conducted, involving 198 Praewa silk weavers from four provinces in the Northeast region of Thailand. Data collection was facilitated through a two-part research tool. The first part included a questionnaire assessment using demographic information, workplace conditions, and self-reported MSDs. The second part involved an ergonomic risk assessment using rapid upper limb assessment (RULA) and hand activity level (HAL). Descriptive statistics and multiple logistic regression analyses were conducted to determine the prevalence and associated factors of MSDs among participants. The findings revealed that the prevalence rates of MSDs in the past 7 days and 12 months were 68.68% and 96.46%, respectively. The highest prevalence rates of MSDs (over 60.00%) were observed in the wrists, fingers, and neck, with similar trends reported in both the past 7 days and 12 months. Key factors associated with MSDs over the past 12 months included low hand strength test results (adjusted odds ratio (AOR)=2.09; 95%CI: 0.44–11.05), quite low hand strength test results (AOR=2.49; 95%CI: 0.29–21.15), weaving experience of 21–30 years (AOR=1.07; 95%CI: 0.20–5.64), age between 31–40 years  (AOR=2.63; 95%CI: 0.49–13.91), age above 41 years (AOR=1.13; 95%CI: 1.08–1.19), RULA level 4 (AOR=3.62; 95%CI: 0.66–19.96), and HAL score exceeding 0.78 (AOR=0.63; 95%CI: 0.80–0.98) were significantly associated with MSDs during the past 12 months. This study highlights the high prevalence of MSDs among Praewa silk weavers, attributed to occupational risk factors such as low hand strength, high hand activity level, extensive weaving experience, and poor working posture. The weaving process itself is a significant contributor to these disorders. In conclusion, ergonomics interventions aimed at preventing MSDs, including postural training, injury prevention programs, and re-designed pull-cloth devices, are recommended to mitigate these risks.